(untitled) (Journal of Management & Business, 2021)
Training is the process that allows the organization, develop the learning capacity of its members, through the modification of knowledge, skills and attitudes, directing it to action to face and solve problems of the job. In two companies from the center of the country, one in mining sector and the another in food sector, we do not know the benefits of investment of training in workers. Therefore, we use statistical techniques, defining key performance indicators (KPI) and diagnosing the current management of measuring the impact of training in each organization. In some cases we find that the impact of training on productivity is significant and in other cases it is not.